2007
DOI: 10.1007/s10706-006-9107-2
|View full text |Cite
|
Sign up to set email alerts
|

Stress induced time dependent behavior of clayey soils

Abstract: It is shown that time compression curve obtained from one-dimensional consolidation curve in the laboratory may include six phases. These are initial compression, first primary compression, transition from first primary compression to second primary compression, second primary compression, and transition from second primary compression to creep and lastly creep. This paper attempts to identify the quantitative beginnings and characteristics of these phases. A mathematical characteristic of all the soils that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…It was shown that difference in c v values was insignificant. Tewatia (1998), Tewatia et al (2007,) and Tewatia (2010) divided Terzaghi's Eq. 2 into 3 parts in 40:20:40 ratio.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that difference in c v values was insignificant. Tewatia (1998), Tewatia et al (2007,) and Tewatia (2010) divided Terzaghi's Eq. 2 into 3 parts in 40:20:40 ratio.…”
Section: Discussionmentioning
confidence: 99%
“…10 and 13, it can be shown that it leads to the following experimental Eq. 32 (Tewatia 2010;Tewatia et al 2012Tewatia et al , 2013 …”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…After 60 % consolidation vertical consolidation and radial consolidation, both are linear on d-dd/dt plot (Tewatia 1998(Tewatia , 2010Tewatia et al 2007Tewatia et al , 2012Tewatia et al , 2013. Here, the lines OA and OB are the lines joining points O and A, and O and B.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
See 2 more Smart Citations